HOMO CULTURALIS VERSUS CULTURA ANIMI - Maturkanič, Patrik; Tomanova Cergetova, Ivana; Kondrla, Peter; Kurilenko, Viktoria; Martin , Jose Garcia (Journal of Education Culture and Society, 2021)
Aim. Presented study deals with the cultural dimension. It analyses external and internal human activities, that are creating the polarity develop values. The aim of the study is to clarify and connect the theoretical level of thinking with the reality of life practice, which shows the true meaning of human existence. Concept. The study highlights the importance of human thinking and decision making. Through the actions, one develops and creates the values of human dignity. The study focuses on the importance of two dimensions (horizontal and vertical dimensions of man), the relationship of man to God. Human culture includes behavior that can be learned and is shaped by the environment in which one lives. This contribution is to clarify a culture of thinking that is a reflection of the soul of human being. Since culture is not only a matter of individual dispositions but also of social reality, it is right to underline this dual aspect of the plurality dimension (Binetti et al., 2021). Conclusion. The study identifies a fundamental aspect of the culture’s values, which show the potential of the soul of every human being. Human values influence thinking and actions of human being, thus creating the image of God.